Marketing Performance after Covid-19 Pandemic on Food and Beverage SMEs in Semarang - Ahmad Ali; Teguh Harso Widagdo (Jibaku: Jurnal Ilmiah Bisnis, Manajemen dan Akuntansi, 2022)
The purpose of this study is to analyze how market sensing and consumer need adaptability, can achieve competitive advantage which is then expected to be able to improve marketing performance. This study took as many as 120 respondents who own SMEs Food and Beverage in Semarang, Central Java. The analytical tool used is SEM (Structural Equation Modeling). The results of data analysis for all models have met the criteria of Goodness Of Fit with chi square value = 89.718, degrees of freedom (df) = 100, probability = 0.760, CMIN/DF = 0.897, GFI = 0.914, AGFI = 0.884, TLI = 1.025, CFI = 1,000 and RMSEA = 0.000. Thus it can be said that the proposed research model is acceptable. The results of the analysis prove that market sensing and consumer need adaptability have a significant effect on competitive advantage so as to improve marketing performance.